The Law of Identity Harm - Sarah Dadush (Washington University Law Review, 2019)
Identity harm refers to the anguish experienced by consumers who learn that their efforts to consume in line with their personal values have been undermined by a company’s false or exaggerated promises about its wares. When broken, other-regarding “virtuous promises” about products (e.g., eco-friendly, responsible, fair-trade, cruelty free, conflict free) give rise to identity harm by making consumers unwittingly complicit in hurting others. A leading example is the Volkswagen emissions scandal: when environmentally-conscious purchasers of Volkswagen’s “clean diesel” cars learned that the vehicles were in fact hyper-polluting, they experienced identity harm because of their complicity in a scheme that hurt the planet and the health of their communities. As more people become sensitized to environmental and social (labor and human rights) sustainability challenges, they are also becoming increasingly concerned about their role in aggravating these challenges through their individual consumption. Identity harm surfaces against the backdrop of an under-regulated market for virtuous goods that is expanding to meet the demands of conscious consumers. Troublingly, those who experience identity harm currently have little recourse in private law, which reveals a serious deficit in our legal regime. This Article, one in a series, recommends correcting this protective deficit by operationalizing identity harm under tort, contract, and state consumer law, with a particular focus on the latter.
Keywords: Identity harm; Consumer protection; Environmentally-conscious consumers; Consumer law; Eco-friendly products